2019
DOI: 10.1016/j.numecd.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

A within-sibling pair analysis of lifestyle behaviours and BMI z-score in the multi-centre I.Family study

Abstract: Background and aims: By investigating differences in lifestyle behaviours and BMI in sibling pairs, family-level confounding is minimized and causal inference is improved, compared to cross-sectional studies of unrelated children. Thus, we aimed to investigate within-sibling pair differences in different lifestyle behaviours and differences in BMI z-scores in children and adolescents. Methods and results: We examined three groups of sibling pairs 1) all same-sex sibling pairs with maximum 4 years age differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…One is that ability to compensate for energy in SSBs contributes minimally to siblings’ differences in adiposity. Other factors, such as differences in dietary restraint (Table 5) and physical activity (Roemmich et al, 2010; Bogl et al, 2019) appear to have a greater impact upon sibling differences in body weight. Another possibility is that differences in compensation ability will eventually lead to differences in adiposity but that these differences were not apparent in such a short duration study.…”
Section: Discussionmentioning
confidence: 99%
“…One is that ability to compensate for energy in SSBs contributes minimally to siblings’ differences in adiposity. Other factors, such as differences in dietary restraint (Table 5) and physical activity (Roemmich et al, 2010; Bogl et al, 2019) appear to have a greater impact upon sibling differences in body weight. Another possibility is that differences in compensation ability will eventually lead to differences in adiposity but that these differences were not apparent in such a short duration study.…”
Section: Discussionmentioning
confidence: 99%
“…Other research already showed that family members influence each other’s nutrition behaviors. For example, families have similar dietary intakes [26,27], especially regarding the consumption of healthy nutrition [26]. Our study specifically shows the influence of shared values, routines, and interaction patterns concerning healthy nutrition within a family (defined as the family nutrition climate) on the child’s nutrition behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The logic of extended pedigree studies is to collect information on relatives having different genetic and environmental relatedness, thus allowing for estimation of genetic and environmental variation. However, in some cases even just collecting information on nuclear families is enough if the interest is only to take into account the total familial effect combining genetic factors and shared environment (Bogl et al, 2019). The history of family studies on BMI goes back to the early 20 th century when it was first shown that obesity clusters in families, indicating the importance of genetic factors (Davenport, 1923).…”
Section: Extended Pedigree Studiesmentioning
confidence: 99%